Diretrizes curriculares para o ensino de Língua Portuguesa: poder e produção de subjetividade - Martins, Andre Luis Batista (2015)
This thesis discusses the relationship between Portuguese Language teachers from Secretaria Municipal de Educação de Uberlândia and the Curriculum Guidelines for the Portuguese Language Teaching (DCELP). In particular, this relationship was investigated from a review of the document undertaken by a group of teachers designated for such a purpose. Thus, the overall goal of the research is the discussion of these guidelines as a reference tool for Portuguese teachers. The guiding hypothesis of this study assumes that there are relations of power exercised by both DCELP and teachers. This exercising of power produces a resistance that becomes evident through the way teachers silence the DCELP. The hypothesis also takes into account that this resistance is not necessarily reversed in favor of a relationship with the teaching of Portuguese language that would be differentiated and able to promote shifts. Methodologically, the corpus of the research consists of two groups of discursive excerpts. The first is from a search form addressed to the group of teachers who have reviewed the DCELP in 2011. The second comes from the teaching annual plans drawn up by Portuguese teachers. Theoretically, the research sought to support the dialogue between the discursive approach as understood by Foucault and theoretical contributions brought by Discourse Analysis, especially as developed by Michel Pêcheux. Concepts such as power, discursive practices, interdiscourse, intradiscourse and resistance composed the theoretical framework. In general, the results of the analysis confirm the hypothesis. The utterances enunciated by the review team analyzed showed that silencing of DCELP occurs by a theoretical lack of teachers to what concerns the understanding of the methodological and theoretical proposals found in the DCELP. Similarly, the teaching plans analyzed indicated that there is a distance between the propositions of DCELP and the theoretical purposes mobilized for its preparation. In both analyzed discursive excerpts, the effect of silencing the guidelines makes their potential, with respect to their theoretical and methodological proposals for the teaching of Portuguese, reduced. As a result, resistance to DCELP does not produce a different relationship with the teaching of Portuguese.